Deep carbon : past to present - Orcutt, Beth, 1980-; Daniel, Isabelle, 1968-; Dasgupta, Rajdeep, 1976- (Cambridge : Cambridge University Press, 2020)
Carbon is one of the most important elements of our planet, and ninety percent of it resides inside Earth's interior. This book summarizes ten years of research by scientists involved in the Deep Carbon Observatory, a global community of 1200 scientists. It is a comprehensive guide to carbon inside Earth, including its quantities, movements, forms, origins, changes over time, and impact on planetary processes. Leading experts from a variety of fields, including geoscience, biology, chemistry, and physics, provide exciting new insights into the interconnected nature of the global carbon cycle, and explain why it matters to the past, present, and future of our planet. With end-of-chapter problems, illustrative infographics, full-color images, and access to online models and datasets, it is a valuable reference for graduate students, researchers, and professional scientists interested in carbon cycling and Earth system science. This title is also available as Open Access on Cambridge Core.
Title from publisher's bibliographic system (viewed on 11 Oct 2019).
Keywords: Carbon; Carbon cycle (Biogeochemistry); Earth (Planet) -- Crust; Earth (Planet) -- Mantle